2019
DOI: 10.1111/dth.13159
|View full text |Cite
|
Sign up to set email alerts
|

Rejuvenation of periocular region in Koreans: A multimodal approach combining botulinum toxin, fillers, and micro‐focused ultrasound with visualization for optimal results

Abstract: Periorbital aging involves all layers of the skin, fat, and the bony orbit. Therefore, a multimodal approach is necessary. Twenty Korean subjects who required periorbital rejuvenation were enrolled in this study. First, micro-focused ultrasound with visualization (MFU-V) was performed across the supra-brow area, lateral canthus, and the infraorbital area. Next, the filler was injected into the sunken upper eyelid, lateral eyebrow, and the infraorbital area. Lastly, botulinum toxin was administered into the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 29 publications
0
20
0
1
Order By: Relevance
“…1 The botulinum toxin acts by blocking the acetylcholine release at the site of motor endplate causing muscle paralysis. 2,3 Its action involves the selective paralysis of certain muscles but inadvertent paralysis of adjacent or other muscles can cause adverse effects. 4,5 It has been demonstrated that intradermal injection of botulinum toxin can be considered as an effective method for facial rejuvenation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The botulinum toxin acts by blocking the acetylcholine release at the site of motor endplate causing muscle paralysis. 2,3 Its action involves the selective paralysis of certain muscles but inadvertent paralysis of adjacent or other muscles can cause adverse effects. 4,5 It has been demonstrated that intradermal injection of botulinum toxin can be considered as an effective method for facial rejuvenation.…”
Section: Introductionmentioning
confidence: 99%
“…Botulinum toxins are commonly used in esthetic practice for beautification of a face, that is, the correction of wrinkles and laxity 1 . The botulinum toxin acts by blocking the acetylcholine release at the site of motor endplate causing muscle paralysis 2,3 . Its action involves the selective paralysis of certain muscles but inadvertent paralysis of adjacent or other muscles can cause adverse effects 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…As ondas ultrassônicas promovem um aquecimento no interior do tecido, induzindo a degradação do colágeno antigo e quaternariamente desestruturado. As ondas ultrassônicas permitem a propagação de energia de maneira focalizada e controlada [8].…”
Section: Figura 2 -Foto Da Voluntária Caso 2 No Momento a Antes Do In...unclassified
“…The desire to reverse signs of aging has led to the rise of various rejuvenation techniques, 1‐4 and with a trend shift toward minimally invasive treatment, botulinum toxin injection has become increasingly popular 5 …”
Section: Introductionmentioning
confidence: 99%
“…The desire to reverse signs of aging has led to the rise of various rejuvenation techniques, [1][2][3][4] and with a trend shift toward minimally invasive treatment, botulinum toxin injection has become increasingly popular. 5 Botulinum toxin (BTX) inhibits presynaptic acetylcholine release at the targeted neuromuscular junction and has been the treatment of choice for dynamic wrinkles (i.e., glabellar rhytids, crow's feet, forehead lines) since 2002.…”
Section: Introductionmentioning
confidence: 99%